2-Deoxy-D-glucose, not mercaptoacetate, induces a reversible reduction of body temperature in male desert hamsters (Phodopus roborovskii). (January 2018) - Chi, Qing-Sheng; Li, Xiu-Juan; Wang, De-Hua
Abstract: The initiation of torpor is supposed to be related to the availability of metabolic fuels. Studies on metabolic fuel inhibition of glucose by using 2-deoxy-D-glucose (2DG) or fatty acid by mercaptoacetate (MA) in heterothermic mammals produced mixed outcomes. To examine the roles of availability of glucose and fatty acid in the initiation of torpor in desert hamsters ( Phodopus roborovskii ), we intraperitoneally administrated 2DG and MA to summer-acclimated male hamsters while body temperature (Tb ), metabolic rate (MR) and respiratory quotient (RQ) were simultaneously recorded to monitor their thermoregulatory response. 2DG induced a reversible reduction of Tb in desert hamsters both at ambient temperature (Ta ) of 23 °C and 5 °C. At Ta of 23 °C, Tb, MR and RQ decreased in a dose-dependent manner with a large Tb -Ta differential (> 6.5 °C) and a lowest Tb of 28.0 °C which were comparable to those in fasted hamsters. At Ta of 5 °C, 2DG-treated hamsters also decreased Tb to the same level as at Ta 23 °C, but MR was significantly higher than that at Ta of 23 °C at each dose, suggesting doses of 2DG directly affected the hypothalamic Tb set-point. Different from fasted hamsters which maintain normothermic at Ta of 5 °C, 2DG-treated hamsters showed a substantial reduction of Tb at Ta 5 °C, indica ting an overwhelming effect on the thermoregulatory system regardless of Ta . Furthermore, the rapid decrease of Tb and outstretched body posture in 2DG-treated hamsters suggest that the effects of 2DG were not simply mimicking the torpor pathways but that other mechanisms are involved. Interestingly, MA failed to induce a torpor-like state in male desert hamsters. Our results suggest that availability of glucose rather than fatty acid plays an important role for initiation of torpor in desert hamsters. Highlights: Metabolic rate, body temperature and respiratory quotient were monitored simultaneously in 2DG or MA-treated hamsters. 2DG induced a profound reversible reduction of Tb which is comparable to that in fasted hamsters. 2DG treatment seemed to have an overwhelming effect on the hypothalamic Tb set-point regardless of ambient temperature. MA was not effective to induce a torpor-like state in these hamsters.